A study on the factors influencing the use of mobile banking among employees of Euromobil, Glenmarie / Ros Ashiqin Muhammed Saleh - Muhammed Saleh, Ros Ashiqin (2015)
The aim of this study is to investigate the factors that determine the intention of using mobile banking among the employees of Euromobil, Glenmarie. Today, the advancement of mobile technologies has provided lots of opportunities and ideas for financial providers in introducing new financial innovations. This includes the use of mobile banking. However, with the help of technologies, criminal exposure arises as well. This is due to the vulnerability received from the technologies itself. Viruses that spread into these mobile devices have given an easy pass towards the hackers. Hence, this study extends the applicability of the Technology Acceptance Model (TAM) to mobile banking that includes perceived usefulness, perceived ease of use, perceived credibility, and perceived self-efficacy as the independent variable. The reason is to identify the factors of using mobile banking regardless of the problem that is possible to occur. The study contains a sample of employees working in Euromobil, Glenmarie and 150 sets of questionnaires are distributed. The results indicate that perceived usefulness and perceived credibility are important determinants in predicting the intentions of Euromobil employees to use mobile banking. However, perceived ease of use and perceived self-efficacy provide insignificant result towards the usage of the banking services. The results of the studies also provide general guidelines to banking institutions for better arrangement of mobile banking services as their future device on banking facilities.